2022
DOI: 10.1101/2022.01.03.22268687
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic modifiers of Huntington’s disease differentially influence motor and cognitive domains

Abstract: Genome-wide association studies (GWAS) of Huntington’s disease (HD) have identified six DNA maintenance gene loci (among others) as modifiers and implicated a two step-mechanism of pathogenesis: somatic instability of the causative HTT CAG repeat with subsequent triggering of neuronal damage. The largest studies have been limited to HD individuals with a rater-estimated age at motor onset. To capitalize on the wealth of phenotypic data in several large HD natural history studies, we have performed algorithmic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…We did not find a significant association between FAN1, MAPT, BDNF and COMT variants and global cognitive function at baseline or change over time after Bonferroni correction for five multiple comparisons (all pbon > 0.068; Table 3). In agreement with previous analyses of disease progression in the same cohort 25 and recent research 15 , MSH3 was a significant predictor of global cognitive function at baseline and change (both pbon = 0.045; Table 3 and Supplementary Table 9). More specifically, participants with one or more 3a alleles in MSH3 had better cognitive function at baseline and slower cognitive decline compared to non-carriers of 3a alleles (for average age and DBS slope (95% CI) = -0.329 (-0.434, -0.223) and -0.118 (-0.241, 0.004) for non-carriers and carriers respectively; contrast estimate (SE) non-carriers vs carriers = -0.21 (0.081), t-value(213) = -2.587, p-value = 0.010; Figure 2A and Supplementary Figure 4).…”
Section: Genetic Polymorphismssupporting
confidence: 90%
See 4 more Smart Citations
“…We did not find a significant association between FAN1, MAPT, BDNF and COMT variants and global cognitive function at baseline or change over time after Bonferroni correction for five multiple comparisons (all pbon > 0.068; Table 3). In agreement with previous analyses of disease progression in the same cohort 25 and recent research 15 , MSH3 was a significant predictor of global cognitive function at baseline and change (both pbon = 0.045; Table 3 and Supplementary Table 9). More specifically, participants with one or more 3a alleles in MSH3 had better cognitive function at baseline and slower cognitive decline compared to non-carriers of 3a alleles (for average age and DBS slope (95% CI) = -0.329 (-0.434, -0.223) and -0.118 (-0.241, 0.004) for non-carriers and carriers respectively; contrast estimate (SE) non-carriers vs carriers = -0.21 (0.081), t-value(213) = -2.587, p-value = 0.010; Figure 2A and Supplementary Figure 4).…”
Section: Genetic Polymorphismssupporting
confidence: 90%
“…Intellectual enrichment did not interact with any of the other genetic polymorphisms we examined, whereas the only genetic predictor with a significant effect on cognitive function was variation in MSH3. A recent study 15 has identified MSH3 as a modifier of cognitive function in HD, while we have previously shown in this cohort that variation in MSH3, specifically carrying a 3a allele, has a protective effect on a composite score of disease progression which included cognitive and psychomotor function 22,25 . It is currently hypothesized that MSH3 is introducing an expansion of the HTT CAG repeat in the process of repair.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations